Modeling investigation of the impacts of dead-end fracture on heat transfer of water flowing through rough fractured rocks. Issue 2 (October 2020) - Chen, Yuedu
Abstract: A clear understanding of the convective heat transfer characteristics of fluid in three-dimensional (3D) rock fractures affected by dead-end fractures is important in evaluating heat recovery in fractured geothermal reservoirs. Two 3D cubic fractured rock models with and without rough dead-end fractures are built to conduct flow and heat transfer simulations by solving hydrothermal coupling equations. The rough fractures are upscaled from lab-measured small-scale rock fractures. Injection velocities of 0.002 m/s and 0.02 m/s were imposed to examine how dead-end fractures affect the heat transfer processes within hot fractured rocks. Several characteristic parameters, including outlet water temperature, total heat extraction, and overall permeability, are presented to quantitatively describe the effects of dead-end fractures. Results show that dead-end fractures retard fluid flow through the fractured model and significantly decrease the overall permeability. A low-temperature zone grows rapidly under the effect of dead-end fractures, and the outlet water temperature is lower in this case than in the model without dead-end fractures. Moreover, the total heat extraction is higher in the model without dead-end fractures than in the model with dead-end fractures. This result is mainly ascribed to the former model's large overall permeability. Results reveal that dead-end fractures cannot be ignored in the evaluation of flow and heat transfer in the modeling of heat extraction from subsurface fractured geothermal reservoirs.